Spatial partitioning of kefir microbial consortia by 3D bioprinting: A strategy to facilitate non-contact metabolic cross-talk and fermentation efficacy - Deyi Huang; Dev Raj Acharya; Jiaqi Luo; Qihe Chen; Ying Shi (Food Research International, 2026)

Waste to Wealth: Acidulated Organic Manures for Enhanced Productivity and Nutrient–Supplying Capacity of Alkaline Soils - Sandeep Bedwal; Nirmalendu Basak; Arvind Kumar Rai; Parul Sundha; Priyanka Chandra; Dev Raj; Anita Mann; Subedar Patel; Harspreet Kaur; Sanjay Kumar; Raksh Vir Jasra; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2026)

Impact of bacterial cellulose nanofibril on mechanical integrity and essential oil release dynamics in electrospun gelatin/PVA films for duck meat packaging - Dev Raj Acharya; Pankaj Koirala; Siyu Liu; Jiaqi Luo; Bijie Wang; Dafaallah Albashir; Qihe Chen; Ying Shi (Food Chemistry, 2026)

Fluoroquinolone Resistant Enterobacteriaceae Isolated from Bagmati River and its Tributaries in Kathmandu, Nepal - Santosh Khanal; Joshna Thapa; Deepa Neupane; Suman SK; Sudeep K C; Tista Prasai Joshi; Dev Raj Joshi (Water, Air, & Soil Pollution, 2026)

Corrigendum to “Bioengineering of Pickering emulsion integrated pH-responsive gelatin film: Mechanistic insights into controlled release and safety assessment of duck meat”, 50 (2025), 101550 - Dev Raj Acharya; Shuai Bian; Siyu Liu; Jiaqi Luo; Pankaj Koirala; Dafaallah Albashir; Qihe Chen; Ying Shi (Food Packaging and Shelf Life, 2025)

Investigation of bacterial communities and antibiotic-resistant bacteria in the aquatic environments from Kathmandu, Nepal - Santosh Khanal; Sudeep K C; Tista Prasai Joshi; Ziming Han; Yu Zhang; Min Yang; Dev Raj Joshi (Journal of Environmental Chemical Engineering, 2025)

Bioengineering of Pickering emulsion integrated pH-responsive gelatin film: Mechanistic insights into controlled release and safety assessment for duck meat - Dev Raj Acharya; Shuai Bian; Siyu Liu; Jiaqi Luo; Pankaj Koirala; Dafaallah Albashir; Qihe Chen; Ying Shi (Food Packaging and Shelf Life, 2025)

Leaf Chlorophyll Concentration Estimation Using Absorption Spectroscopy of AVIRIS-NG for a Mangrove Forest in India - Somnath Paramanik; Mukunda Dev Behera; Nikhil Raj Deep; Surbhi Barnwal; Bimal Kumar Bhattacharya; Soumit Kumar Behera; Dillip Kumar Swain; Jadunandan Dash (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)

Hydrogeochemical characterization of shallow and deep groundwater for drinking and irrigation water quality index of Kathmandu Valley, Nepal - Manisha Ghimire; Naina Byanjankar; Tejendra Regmi; Rachna Jha; Dev Raj Joshi; Tista Prasai Joshi (Environmental Geochemistry and Health, 2025)

Long-term longitudinal monitoring of SARS CoV-2 in urban rivers and sewers of Nepal - Sarmila Tandukar; Niva Sthapit; Ocean Thakali; Rakshya Baral; Ananda Tiwari; Jivan Shakya; Reshma Tuladhar; Dev Raj Joshi; Bhawana Sharma; Bhushan Raj Shrestha; Samendra P. Sherchan (Science of The Total Environment, 2024)

A novel polydiacetylene-functionalized fibrinogen paper-based biosensor for on-spot and rapid detection of Staphylococcus aureus - Dafaallah Albashir; Hongyun Lu; Mostafa Gouda; Dev Raj Acharya; Umar Abdulbaki Danhassan; Abdelmoneim Bakur; Ying Shi; Qihe Chen (Food Chemistry, 2024)

Synthesis and characterization of Neurospora intermedia-based composite mycoprotein gel meat: Insight into the effect of pH and soluble starch on water-holding capacity and texture properties - Bijie Wang; Hongyun Lu; Hanghang Lou; Dev Raj Acharya; Ying Shi; Qihe Chen (Food Hydrocolloids, 2024)

Bacterial biofilm formation in seafood: Mechanisms and inhibition through novel non‐thermal techniques - Sagar Gautam; Nirmala Subedi; Kabita Dhakal; Pankaj Koirala; Dev Raj Acharya; Om Prakash Malav; Fahad Al‐Asmari; Soottawat Benjakul; Nilesh Nirmal (Reviews in Aquaculture, 2024)
Seafoods are susceptible to microbial contamination due to their high moisture, nutrient contents and neutral pH. Among various microorganisms, biofilm‐forming bacteria pose a severe threat to the seafood supply chain as well as consumer health. Bacterial biofilm formation in seafood is primarily caused by Aeromonas hydrophila , Vibrio cholerae , V. vulnificus , V. parahaemolyticus , Salmonella spp., and Listeria monocytogenes. Biofilm formation is an important protective mechanism of microorganisms causing spoilage of seafood and disease threats to consumers. The attachment of microbes on the surface of seafood followed by the growth and proliferation of bacterial cells leads to the production of exopolymer compounds and the formation of biofilm. This biofilm is difficult to destroy or inhibit through conventional prevention/destruction techniques. The occurrence of bacterial strains/biofilms with more resistance to different preventive strategies is a big challenge for the seafood processing industry. This review covers the mechanisms of biofilm formation by bacteria and various non‐thermal processing approaches to prevent microbial contamination and biofilm formation in seafood products. The aforementioned non‐thermal processing techniques for the destruction of biofilm and quality control of seafood products include cold plasma treatment, irradiation, pulsed electric field technology, hydrostatic pressure processing, photosensitisation, natural bioactive compounds and so on. All these techniques effectively inhibit the bacterial biofilm and microbial growth without altering sensorial properties. However, further research validation and applications at the industry level are still required.

Extended-spectrum β-lactamase-producing bacteria and their resistance determinants in different wastewaters and rivers in Nepal - Santosh Khanal; Sudeep K C; Tista Prasai Joshi; Ziming Han; Chunzhen Wang; Jyoti Maharjan; Reshma Tuladhar; Dev Raj Joshi (Journal of Hazardous Materials, 2024)

Application of wastewater-based epidemiology for monitoring COVID-19 in hospital and housing wastewaters - Sarmila Tandukar; Ocean Thakali; Rakshya Baral; Ananda Tiwari; Eiji Haramoto; Reshma Tuladhar; Dev Raj Joshi; Samendra P. Sherchan (Science of The Total Environment, 2024)

Removal of Dimethyl Arsenic Acid from Aqueous Solution by Ferric Manganese Binary Oxide - Naina Byanjankar; Tista Prasai Joshi; Agni Dhakal; Dev Raj Joshi; Rashmi Koju; Zenglu Qi; Chengzhi Hu; Ruiping Liu (Water, Air, & Soil Pollution, 2024)

Identification and Characterization of Non-protein Coding RNA Homologs in Serratia Marcescens by Comparative Transcriptomics - Balamurugan Rishen Narayan Dev; Selva Raju Kishan Raj; Suresh V. Chinni; Marimuthu Citartan (Indian Journal of Microbiology, 2024)

Antibiotic resistance determinants among carbapenemase producing bacteria isolated from wastewaters of Kathmandu, Nepal - Sudeep K C; Santosh Khanal; Tista Prasai Joshi; Deegendra Khadka; Reshma Tuladhar; Dev Raj Joshi (Environmental Pollution, 2024)

Converting waste to resource: Utilisation of elemental S and consortia of halo–alkaliphilic S–oxidisers for preparation of acidified compost from organic wastes - Sandeep Bedwal; Nirmalendu Basak; Arvind Kumar Rai; Parul Sundha; Subedar Patel; Dev Raj; Anita Mann; Sanjay Kumar; Priyanka Chandra; Rajender Kumar Yadav (Bioresource Technology Reports, 2023)

Extended-spectrum β-lactamases producing Enterobacteriaceae (ESBL-PE) prevalence in Nepal: A systematic review and meta-analysis - Christina Khadka; Manita Shyaula; Gopiram Syangtan; Shrijana Bista; Reshma Tuladhar; Anjana Singh; Dev Raj Joshi; Lok R. Pokhrel; Prabin Dawadi (Science of The Total Environment, 2023)

Occurrence of Antibiotic-Resistant Bacteria and Their Genes in Bagmati River, Nepal - Pratikshya Shrestha; Tista Prasai Joshi; Sarala Nhemhaphuki; Kusal Sitoula; Jyoti Maharjan; Rosa Ranjit; Prakash Shrestha; Dev Raj Joshi (Water, Air, & Soil Pollution, 2023)

Climate change impacts and adaptation strategies in watershed areas in mid-hills of Nepal - Saara Ranabhat; Suman Acharya; Suraj Upadhaya; Bikash Adhikari; Ram Thapa; Sadhana Ranabhat; Dev Raj Gautam (Journal of Environmental Studies and Sciences, 2023)

High efficient removal of 4-aminophenylarsonic acid from aqueous solution via enhanced FeOOH using Mn(VII) - Tista Prasai Joshi; Rashmi Koju; Hanyang Cheng; Zenglu Qi; Ruiping Liu; Yaohui Bai; Chengzhi Hu; Jianfeng Peng; Dev Raj Joshi (Environmental Science and Pollution Research, 2023)

Moderate resolution LAI prediction using Sentinel-2 satellite data and indirect field measurements in Sikkim Himalaya - Sujoy Mudi; Somnath Paramanik; Mukunda Dev Behera; A Jaya Prakash; Nikhil Raj Deep; Manish P. Kale; Shubham Kumar; Narpati Sharma; Prerna Pradhan; Manoj Chavan; Partha Sarathi Roy; Dhiren G. Shrestha (Environmental Monitoring and Assessment, 2022)

Seasonal taxonomic composition of microbial communal shaping the bioaerosols milieu of the urban city of Lanzhou - Prakriti Sharma Ghimire; Dev Raj Joshi; Lekhendra Tripathee; Pengfei Chen; Wasim Sajjad; Shichang Kang (Archives of Microbiology, 2022)

Molecular breeding of ameliorating commercial pearl millet hybrid for downy mildew resistance - Jyoti Taunk; Asha Rani; Neelam R. Yadav; Dev Vart Yadav; Ram C. Yadav; Kushal Raj; Ramesh Kumar; H. P. Yadav (Journal of Genetics, 2018)

Water Quality, Pollution Source Apportionment and Health Risk Assessment of Heavy Metals in Groundwater of an Industrial Area in North India - Rakesh Bhutiani; Dipali Bhaskar Kulkarni; Dev Raj Khanna; Ashutosh Gautam (Exposure and Health, 2016)

Radioprotection to small intestine of the mice against ionizing radiation by semiquinone glucoside derivative (SQGD) isolated from Bacillus sp. INM-1 - Dev Dutt Patel; Deen Dayal Bansal; Saurabh Mishra; Rajesh Arora; Ashok Sharma; Swatantra Kumar Jain; Raj Kumar (Molecular and Cellular Biochemistry, 2012)

Antioxidative and radioprotective activities of semiquinone glucoside derivative (SQGD) isolated from Bacillus sp. INM-1 - Raj Kumar; Deen Dayal Bansal; Dev Dutt Patel; Saurabh Mishra; Yana Karamalakova; A. Zheleva; Vessilina Gadjeva; Rakesh Kumar Sharma (Molecular and Cellular Biochemistry, 2011)